Optimized basis sets for the calculation of indirect nuclear spin-spin coupling constants involving the atoms B, Al, Si, P, and Cl - Provasi, Patricio Federico (2010)
The aug-cc-pVTZ-J series of basis sets for indirect nuclear spin-spin coupling constants has been extended to the atoms B, Al, Si, P, and Cl. The basis sets were obtained according to the scheme previously described by Provasi et al. [J. Chem. Phys. 115, 1324 (2001)]. First, the completely uncontracted correlation consistent aug-cc-pVTZ basis sets were extended with four tight ss and three tight dd functions. Second, the ss and pp basis functions were contracted with the molecular orbital coefficients of self-consistent-field calculations performed with the uncontracted basis sets on the simplest hydrides of each atom. As a first illustration, we have calculated the one-bond indirect spin-spin coupling constants in BH−4BH4−, BF, AlH, AlF, SiH4SiH4, SiF4SiF4, PH3PH3, PF3PF3, H2SH2S, SF6SF6, HCl, and ClF at the level of density functional theory using the Becke three parameter Lee–Yang–Parr and the second order polarization propagator approximation with coupled cluster singles and doubles amplitudes.